Photoconductive NSOM for mapping optoelectronic phases in nanostructures - Das Anshuman J.; Shivanna Ravichandran; Narayan K.S. (Nanophotonics, 2014)
The advent of optically functional materials with low-intensive processing methods is accompanied by a growing need for high resolution imaging to probe the inherent inhomogeneities in the underlying microstructure. Atomic force microscopy based techniques are typically utilized for imaging the surface of organic thin films, quantum dots and other nanomaterials with ultrahigh resolution. Several modes like conductive, Kelvin, electrostatic amongst others have been particularly successful in imaging the local current, potential and charge distribution of variety of systems. However, the functionality of photoconduction in these materials cannot be directly imaged by these modes alone. There is a requirement for a local excitation source or collection arrangement that is compatible with scanning microscopy techniques followed by a current monitoring mechanism. Near-field scanning optical microscopy (NSOM) possesses all the advantages of scanning microscopy and is capable of local excitation that overcomes the diffraction limit faced by conventional optical microscopes. Additionally, NSOM can be carried out on actual photoconductive two terminal and three terminal device structures to image local optoelectronic properties. In this review, we present the various geometries that have been demonstrated to perform photoconductive NSOM (p-NSOM). We highlight a representative set of important results and discuss the implications of photocurrent imaging in macroscopic device performance.